ANALYSIS OF IDEAL MARRIAGE AGE PERSPECTIVE OF ISLAMIC FAMILY LAW PHILOSOPHY - Lubis, Zulpahmi; Efendi, Rahmad; Rahman, Abdul; Tambunan, Sofwan (UIN Sumatera Utara, 2025)
Abstract: This study aims to analyse the ideal marriage age based on the Islamic family law philosophy perspective in Indonesia. In the context of Islamic family law, the age of marriage is not only seen from the biological aspect, but also from the physical, mental, and social readiness of the individuals involved. This study uses a qualitative method with a legal philosophy approach to explore the values contained in Islamic family law related to the age of marriage. The results of the study show that the ideal age to carry out marriage in Indonesia according to the perspective of Islamic family law philosophy is 21 years old, which is considered the right age to achieve emotional, physical, and mental maturity, so that it can form a family that is sakinah, mawaddah, and rahmah. These findings can be considered in marriage legal policies in Indonesia that prioritise family welfare and social harmony.Keywords: Marital Age, Ideal, Islamic Family Law Philosophy, Indonesia, Legal Policy